A double blind trial of botulinum toxin "A" in torticollis, with one year follow up. Issue 9 (September 1991) - Moore, A P; Blumhardt, L D
Abstract : A double blind placebo controlled crossover trial was performed of botulinum toxin "A" in 20 patients with spasmodic torticollis. There was a statistically significant benefit for those treated with toxin; 12 on toxin improved objectively, compared with four on placebo (p less than 0.04). After a follow up period of one year, 16 still seemed to benefit from repeated toxin injections. The main side effect was dysphagia, which appeared to be dose related in individual patients.